Controle de fretes nacionais como vantagem competitiva nas organizações: estudo de caso em uma indústria do Polo Industrial do Amazonas - Silva, Kamylla Rielly Costa da (Brasil, 2024)
With increased competitiveness between organizations, businesspeople have understood the need to innovate and invest in tools that assist in the management process and enable greater assertiveness in decision-making. Therefore, controlling logistics costs within an organization is extremely important to guarantee competitive advantage, in addition to reducing unnecessary costs in a process that, despite being extremely essential, tends to be very costly for organizations. In this article, a case study will be carried out where a solution will be presented that will help a medium-sized company in the industrial district of Manaus to improve the national freight quotation process, which will enable the reduction of time to carry out this activity, providing, Likewise, cost reduction and greater data accuracy. The work will present a qualitative approach where direct and non-participatory observation, semi-structured interviews and numerical data collection were carried out.